Photosensitizing effects of In vitro crystal violet on photodynamic therapy for Candida albicans - Pinheiro, Rachel Christina de Queiroz (2018)
This study aimed at evaluating the action of the in vitro dye crystal violet on Candida albicans, isolated or as a photosensitizing tool, when compared to methylene blue in photodynamic therapy. It was an experimental and quantitative research. The ATCC 1106 Candida albicans strain was inoculated with an overnight103 UFC/ml. 50µl of the fungal suspension (overnight) were added to 18,0ml of Saboraud agar. To this, 0.2ml of the crystal violet dye was added at 1% and plated. A five-minute period of pre-irradiation was conceded to the sample, after which the red laser was applied.  The dosage applied was that of 100J/cm², with a total energy of 3J. After that, the samples were subcultured in Saboraud agar at 37ºC, for 1 hour. After this period, an aliquot of 1.0 ml was diluted in 9.0 ml of 0.85% sterilized saline solution. 0.1 ml of the diluted result was plated and cultured in saboraud agar. Three plates were incubated in a growth chamber for micro-organisms at 37ºC, and after 48h, the UFCs/ml were counted. In addition to the 1% crystal violet with the laser, the following groups were analyzed: 1% methylene blue with laser, 1% methylene blue, 1% crystal violet, and the use of the laser with no dying. The analyses were conducted in the IBM SPSS (21.0) software. The Kruskal-Wallis (Mann-Whitney U test) was used as well as the Friedman (Wilcoxon) text, with a significance level ?=5%.  As a result, the 1% crystal violet in conjunction with the laser has an important effect against Candida albicans in the photodynamic therapy.